EFEKTIFITAS TAUMA HERBAL DRINK TERHADAP INTENSITAS DISMENOREA - Cia ' Novita; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrak Every fertile woman will menstruate, which normally complain of symptoms of the first two days. The most common physicial symptom is dysmenorrhoea. This study was aimed to determine the effectiveness of Tauma herbal drink in intensity of dysmenorrhoea. The design of this research study was